Endocervical Gram stain smears and their usefulness in the diagnosis of Chlamydia trachomatis. Issue 2 (1st April 2001) - Myziuk, Linda; Romanowski, Barbara; Brown, Myrna
Abstract : Objective: To evaluate the usefulness of endocervical Gram stain smears in the diagnosis of Chlamydia trachomatis and Neisseria gonorrhoeae in a female population attending a STD clinic. Methods: 494 females attending a STD clinic and undergoing a speculum examination had endocervical specimens submitted for C trachomatis culture, direct fluorescent antibody testing (DFA), and N gonorrhoeae culture. Endocervical smears were also collected for Gram stain. The number of polymorphonuclear leucocytes (PMN) per high power field (HPF), presence of bacteria, yeast, red blood cells, and clue cells were recorded. Clinical signs of cervicitis were also documented. Results: N gonorrhoeae was isolated from one subject who was co-infected with C trachomatis and no further analysis was done regarding N gonorrhoeae . Analysis was performed on 220 participants. The prevalence of C trachomatis infection was 13%. Of the Gram smears collected, 55% were inadequate owing to the presence of vaginal contamination. There were an equal number of C trachomatis isolates in patients with ≤10 PMN/HPF (48%) and >10 PMN/HPF (52%). Endocervical mucopus and erythema were statistically significant for the presence of C trachomatis (p<0.001 and 0.02 respectively). The presence of any signs of cervicitis—that is, mucopus, friability, erythema, and ectropion together with >10 PMN/HPF was statistically significant for the presence of C trachomatis . Conclusion: The use of endocervical Gram smear results together with clinical information can be used to identify high risk women for C trachomatis infection.